A Qualitative Approach In Designing Differentiated Numeracy Learning Strategies for Lower Grade Slow Learner Students - Arizkylia Yoka Putri; Neni Mariana; Hitta Alfi Muhimmah (Didaktika: Jurnal Kependidikan, 2024)
Slow learners often face difficulties in grasping abstract mathematical concepts, necessitating adaptive teaching strategies. The purpose of this study is to design an effective learning strategy using a concrete object-based approach his research utilizes a qualitative approach, combining case studies and a systematic literature review. Data was collected through classroom observations, teacher interviews, and document analysis were conducted to assess current instructional strategies and to identify gaps in supporting slow learners. The literature review synthesized findings from relevant studies, highlighting the importance of concrete, visual, and manipulative media in numeracy instruction for slow learner students. The findings indicate a significant improvement in slow learner students' ability to recognize numbers and relate them to physical objects and shapes. The discussion highlights that the five activities designed, namely counting objects, matching numbers with the number of objects, grouping objects, recognizing flat shapes, and drawing, can improve students' numerical understanding, where this approach not only helps students recognize numbers but also builds relationships between numbers and objects around them. The implications of this study emphasize the importance of using concrete aids and flexible teaching strategies in learning for slow learner students, as well as the need for collaboration between teachers and parents to support a more inclusive and effective learning process.